2014
DOI: 10.1016/j.cct.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of a telehealth-enhanced intervention for pain and symptom management

Abstract: Managing chronic pain effectively is often challenging for health care providers and patients. Telehealth technologies can bridge geographic distance and improve patients' quality of care in communities where access to pain specialists has previously been unavailable. This paper describes the development and evaluation of a telehealth intervention (TelePain) designed to address the need for pain specialist consultation regarding pain and symptom management issues in non-academic medical centers. We describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…All 39 remaining articles were then downloaded as PDF files for full-text peer review and discussion [ 13 - 16 , 21 , 22 , 38 - 70 ]. We excluded 23 articles after the full-text screening for the following reasons: (1) a device or program feasibility study (n=2) [ 66 , 69 ], (2) duplicated article (n=1) [ 21 ], (3) not an intervention study (n=5) [ 39 , 43 , 47 , 49 , 53 ], (4) not a mobile phone intervention (n=7) [ 14 , 42 , 48 , 56 , 58 , 63 , 68 ], (5) no sleep outcome (n=3) [ 16 , 44 , 65 ], and (6) a protocol or trial (n=5) [ 40 , 45 , 50 - 52 ]. The entire selection procedure was independently performed by two researchers (JCS and JK), and then the research team resolved differences by discussion.…”
Section: Resultsmentioning
confidence: 99%
“…All 39 remaining articles were then downloaded as PDF files for full-text peer review and discussion [ 13 - 16 , 21 , 22 , 38 - 70 ]. We excluded 23 articles after the full-text screening for the following reasons: (1) a device or program feasibility study (n=2) [ 66 , 69 ], (2) duplicated article (n=1) [ 21 ], (3) not an intervention study (n=5) [ 39 , 43 , 47 , 49 , 53 ], (4) not a mobile phone intervention (n=7) [ 14 , 42 , 48 , 56 , 58 , 63 , 68 ], (5) no sleep outcome (n=3) [ 16 , 44 , 65 ], and (6) a protocol or trial (n=5) [ 40 , 45 , 50 - 52 ]. The entire selection procedure was independently performed by two researchers (JCS and JK), and then the research team resolved differences by discussion.…”
Section: Resultsmentioning
confidence: 99%
“…This has the potential to translate into an increased rate of successful treatments of future patients, not only those treated by CoP members, but others treated in their clinic. A study is currently underway to test the effectiveness of TelePain on patient outcomes [18]. …”
Section: Resultsmentioning
confidence: 99%
“…Geographic barriers, underinsurance, and referral practices limit access to pain specialists. 20,21 Among opioid-naïve patients with new persistent use, we found that utilization of PM&R/Pain Medicine for opioid prescriptions varied among geographic regions. Also seen in Table 1, PM&R/Pain Medicine physicians were more likely to prescribe opioids following minor surgeries to older patients that have an education level of at least a bachelor degree, increased comorbidities, and pain disorders.…”
Section: Discussionmentioning
confidence: 95%